An experimental study and analysis of various cylindrical pin diameters in friction stir welded AA7075-T6 and A384.0-T6 aluminium alloys of butt joint. (2021) - Anganan, K.; Prabagaran, S.; Marimuthu, S.
Abstract: The Friction Stir Welding is one of the solid state pressure welding processes. To evaluate the joint characteristics, the three factors viz. Speed of the Tool rotation, Speed of weld process and various diameters of cylindrical pin are taken in to account. Without using any filler material, the two materials are joined by the application of the stirring action and an applied axial load using rotation of welding tool. The tool design, size and the shape will vary according to the material to be joined. The aim of the design of the tool is not to remove the materials but to develop the sufficient heat and the uniform mixing of the materials to join work pieces. During the mixing of the materials, the flow of the materials will affect the welding quality. So tooling design, size and shapes are the most important factors. In this article same thickness of the aluminium dissimilar materials were used with different diameters of the tool pin in cylindrical shape. The design of Experimental investigation has been performed and subsequently the major finding has been discussed. The ultimate tensile strength has been identified as 102.98 MPa.